A prospective multicenter study on genome wide associations to ranibizumab treatment outcome for age-related macular degeneration - Kenji Yamashiro (Nature Portfolio, 2017)
Abstract We conducted a genome-wide association study (GWAS) on the outcome of anti-VEGF treatment for exudative age-related macular degeneration (AMD) in a prospective cohort. Four hundred and sixty-one treatment-naïve AMD patients were recruited at 13 clinical centers and all patients were treated with 3 monthly injections of ranibizumab followed by pro re nata regimen treatment for one year. Genomic DNA was collected from all patients for a 2-stage GWAS on achieving dry macula after the initial treatment, the requirement for an additional treatment, and visual acuity changes during the 12-month observation period. In addition, we evaluated 9 single-nucleotide polymorphisms (SNPs) in 8 previously reported AMD-related genes for their associations with treatment outcome. The discovery stage with 256 patients evaluated 8,480,849 SNPs, but no SNPs showed genome-wide level significance in association with treatment outcomes. Although SNPs with P-values of <5 × 10−6 were evaluated in replication samples of 205 patients, no SNP was significantly associated with treatment outcomes. Among AMD-susceptibility genes, rs10490924 in ARMS2/HTRA1 was significantly associated with additional treatment requirement in the discovery stage (P = 0.0023), and pooled analysis with the replication stage further confirmed this association (P = 0.0013). ARMS2/HTRA1 polymorphism might be able to predict the frequency of injection after initial ranibizumab treatment.